Impact of workplace spirituality on job satisfaction: Mediating effect of trust - Misbah Hassan; Ali Bin Nadeem; Asma Akhter (Cogent Business & Management, 2016)
Workplace spirituality is a renowned topic now-a-days and is gaining gratitude and value among academicians and industrial people. Workplace spirituality (WPS) aims at meaningful work, sense of community, and value of organization. The purpose of the present study is to examine the relationship between workplace spirituality dimensions and work satisfaction by taking trust as a mediator. Using convenience sampling, a five-point Likert scale questionnaire is used to get data from teachers working in the education sector. Two hundred questionnaires were rotated in universities and 174 responses were generated. Multiple regression is used to test the hypotheses of the study using Barron and Kenny's method. The results showed that WPS has a significantly positive relationship with trust and trust significantly mediates the impact of workplace spirituality on job satisfaction. In future, new dimensions should be added to workplace spirituality. New moderators should be checked along with the mediator. Creativity in the form of improved communication among the teachers can be generated with the help of the promotion of workplace spirituality. The findings indicated that there is a positive relationship between WPS and job satisfaction and trust between employees would mediate the interaction of WPS and job satisfaction as the p-values are less than .05.
Keywords: 650